CAPRi collective action to secure property rights for the poor: avoiding elite capture of natural resource benefits and governance systems - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Participatory research with local communities through planning-action-reflection steps attempting to engage in equitable collective action, to secure property rights and to articulate aspirations through development forums. Local officials were also engaged in advocacies for collaborative land use planning and forest resource benefit distribution.